2022
DOI: 10.3390/s22072551
|View full text |Cite
|
Sign up to set email alerts
|

Machine Learning-Based Software Defect Prediction for Mobile Applications: A Systematic Literature Review

Abstract: Software defect prediction studies aim to predict defect-prone components before the testing stage of the software development process. The main benefit of these prediction models is that more testing resources can be allocated to fault-prone modules effectively. While a few software defect prediction models have been developed for mobile applications, a systematic overview of these studies is still missing. Therefore, we carried out a Systematic Literature Review (SLR) study to evaluate how machine learning h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(11 citation statements)
references
References 48 publications
0
9
0
Order By: Relevance
“…34 Recently, the use of health data for disease prediction has shown the potential application of these methods. 35,36 This study demonstrated that the use of machine learning models can accurately predict fracture in RA patients with osteoporosis. As an important branch of supervised learning, the RFC model has been successfully applied to highdimensional and multi-source data reduction of many diseases.…”
Section: Discussionmentioning
confidence: 76%
“…34 Recently, the use of health data for disease prediction has shown the potential application of these methods. 35,36 This study demonstrated that the use of machine learning models can accurately predict fracture in RA patients with osteoporosis. As an important branch of supervised learning, the RFC model has been successfully applied to highdimensional and multi-source data reduction of many diseases.…”
Section: Discussionmentioning
confidence: 76%
“…The articles selected were screened for quality assessment by an instrument proposed and developed for this scientific field [ 39 , 40 ]. Two independent reviewers read all articles retained for qualitative synthesis and scored the 8 items.…”
Section: Methodsmentioning
confidence: 99%
“…Two independent reviewers read all articles retained for qualitative synthesis and scored the 8 items. Each item was scored 2 points if the answer was “yes”, 1 point if the answer was “partial”, and no points if the answer was “no” [ 39 , 40 ]. Hence, the quality ranges between 0 (lowest quality) and 16 (highest quality).…”
Section: Methodsmentioning
confidence: 99%
“…In order to make design decisions for the model to be developed in this study, we conducted a systematic literature review (SLR) study on this topic [26]. We identified nine research questions and applicable papers were reclaimed from digital platforms.…”
Section: Methodsmentioning
confidence: 99%